Hoop atlas : mapping the remarkable transformation of the modern NBA - Goldsberry, Kirk Patrick (Mariner Books, 2024)
"Every few years a talent comes along that disrupts everything we think we know about how the NBA should work. Whether it's scoring, playmaking, or shooting, these are players and tactics that fundamentally challenge how the game is played and what greatness looks like on a basketball court. For a period of time, these players each become an "Atlas" for the league, carrying the weight of the NBA on their shoulders, but also providing the roadmap that points the way to the future of the sport. In tandem, they map out the modern NBA's creation. Goldsberry returns with a highly visual, electrifying tour through the last three decades of NBA history, showing the "Atlas" players that have led us out of the brutishness of 90s hoops and into the wide open spaces of the most skilled era in NBA history. Charting the course from Jordan to Jokic-with plenty of stops along the way for Iverson, Kobe, Curry, and of course Lebron-Goldsberry, who was instrumental in helping spur the NBA's statistical revolution, has designed a vibrant new way to compare and debate the contributions of the best NBA players of all-time. Masterfully connecting NBA past and present through incisive writing and stunning visual statistical analyses, he shows how we've come to this unprecedented moment, a time when offensive efficiency and shooting percentages are higher than ever. Using beautifully designed, four-color shot maps and illustrations, Goldsberry offers a graphic journey through the last thirty years of the NBA that covers up to the 2023 season and is as much fun to look at as it is to read. The end result offers stories and analyses of a select group of NBA superstars that open up lively debates, reveal just how singular their talents truly are, and characterize the dramatic 21st-century metamorphosis of the best basketball league in the world"--